Application of selection Index for enhancing resistance to Cryptocarya irritans and Vibrio alginolyticus in large yellow croaker - Wang, Jiaying; Zhao, Ji; Liu, Bo; Chi, Hongshu; Jiang, Pengxing; Xiao, Junzu; Jiang, Zhou; Miao, Lingwei; He, Qian; Zeng, Junjia; Ke, Qiaozhen; Zhou, Tao; et al. (Frontiers in Veterinary Science, 2025)
Despite the high cost of genotyping and the limited economic return per individual that restricts the use of genome selection technology in aquatic species breeding, integrating multiple traits in a selection index can reduce costs and present a promising direction for fish breeding. The aim of this study was to evaluate the feasibility and performance of breeding for dual resistance traits against C. irritans and V. alginolyticus in large yellow croaker, using a selection index approach. A candidate stock population from the C. irritans resistance strain (GS3) of the F2 generation (n = 560) was genotyped using a 55 K SNP array. A total of 50 broodstock with the highest genomic estimated breeding value (GEBV) ranking for the C. irritans resistance trait were selected to produce the F3 generation, while 50 broodstock with the highest selection index were selected to breed the double trait strain (GS9). In parallel, two populations without selective breeding population (C1and C2) were used as the control group to produce the offspring. The genetic improvement effect of all the breeding lines (GS3, GS9, C1, and C2) was assessed through artificial challenge experiments with C. irritans and V. alginolyticus, respectively. The GWAS result indicated that resistance to V. alginolyticus was a polygenic trait and the heritability of resistance to V. alginolyticus was estimated to be approximately 0.1. The survival rates of GS9 and GS3 were 43.74 and 86.81%, respectively, after 120 h of challenge with C. irritans infection, whereas those of C1 and C2 remained at 0%. Furthermore, the survival rates of GS9 and GS3 were 27.03 and 15.48%, respectively, after 48 h of V. alginolyticus infection, while the survival rates of C1 and C2 were 12.67 and 14.17%, respectively. These results indicate that genetic improvement of multiple traits in large yellow croaker using genomic selection technology is indeed feasible. Moreover, this study provides a valuable reference for advancing multi-trait breeding applications in aquatic species.